2009
DOI: 10.1111/j.1751-9004.2009.00202.x
|View full text |Cite
|
Sign up to set email alerts
|

Age Differences in Affective Well‐Being: Context Matters

Abstract: The study of emotion across the adult lifespan requires an understanding of how life circumstances change with age. With this knowledge, we can predict when age is related to increases in affective well-being and when age no longer confers such benefits. In the current paper, we review research that finds age-related stability and even increases in affective well-being, as well as agerelated strengths in several emotion regulation strategies. We introduce the theory of Strength and Vulnerability Integration to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
104
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(112 citation statements)
references
References 78 publications
7
104
0
1
Order By: Relevance
“…Results indicated that as a group, older adults reported the lowest levels of depressive symptoms. Despite age-related declines across cognitive functioning domains, research has shown that emotion regulation abilities improve with age [11]. Additionally, with increasing age recollections of past events are disproportionally more positive than negative.…”
Section: Introductionmentioning
confidence: 99%
“…Results indicated that as a group, older adults reported the lowest levels of depressive symptoms. Despite age-related declines across cognitive functioning domains, research has shown that emotion regulation abilities improve with age [11]. Additionally, with increasing age recollections of past events are disproportionally more positive than negative.…”
Section: Introductionmentioning
confidence: 99%
“…implicit association tasks, lexical decision tasks) ). However, it seems that -at least for emotion measures -the inconsistent outcomes of such methods (Charles & Piazza, 2009;Kunzmann, Kupperbush, & Levenson, 2005;Seider, Shiota, Wahlen, & Levenson, 2011;Uchino, Birmingham, & Berg, 2010) and the age-related factors (e.g. physical changes of the skin and antihypertensive medication) make it challenging to select an appropriate method and to properly interpret the results.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Baltes, Baltes, and Baltes (1990), Carstensen (1992), Labouvie-Vief (2003), and Charles and Piazza (2009) proposed theories related to the mainly positive affective orientation of older adults. In the social selectivity theory (SST), Carstensen (1992) explained seniors' focus on emotionally gratifying goals by 'the time that is left in life'.…”
Section: Emotional Ageingmentioning
confidence: 99%
See 2 more Smart Citations